Aquafeed formulation - Nates, Sergio F., 1961- (Academic Press, 2015)
'Aquafeed Formulation' provides summaries with examples and formulation techniques specifically to meet the needs of anyone in the aquaculture industry. As feed is the largest single cost item in aquaculture production, and formulating aquaculture feed requires many combinations of several ingredients and nutrient requirements, this book takes a clear, concise approach, providing essential information on formulation and covering relevant available software, feed nutrients, and additives such as enzymes and phytase and conjugated fatty acids, as well as best industry practices to improve aquafeed production.